Hypoxic stress caused apoptosis of MDBK cells by p53/BCL6-mitochondrial apoptosis pathway - Bin Li; Yangjin Baima; Ji De; Dongxu Wen; Yang Liu; Zhuzha Basang; Nan Jiang (Animal Biotechnology, 2024)
Hypoxia is an important characteristic of Tibetan plateau environment. It can lead to apoptosis, but the mechanism of apoptosis caused by hypoxic stress needs further clarification. Here, cattle kidney cell MDBK were used as cell model. The effect of hypoxic stress on apoptosis and its molecular mechanism were explored. MDBK cells were treated with hypoxic stress, apoptosis and mitochondrial apoptotic pathway were significantly increased, and the expression of B-cell lymphoma 6 (BCL6) was significantly decreased. Overexpressing or inhibiting BCL6 demonstrated that BCL6 inhibited the apoptosis. And the increase of apoptosis controlled by hypoxic stress was blocked by BCL6 overexpressing. MDBK cells were treated with hypoxic stress, the expression and the nuclear localization of p53 were significantly increased. Overexpressing or inhibiting p53 demonstrated that hypoxic stress suppressed the expression of BCL6 through p53. Together, these results indicated that hypoxic stress induced the apoptosis of MDBK cells, and BCL6 was an important negative factor for this regulation process. In MDBK cells, hypoxic stress suppressed the expression of BCL6 through p53/BCL6-mitochondrial apoptotic pathway. This study enhanced current understanding of the molecular mechanisms underlying the regulation of apoptosis by hypoxic stress in MDBK cells.